Design and psychometric testing of instruments to measure qualified intensive care nurses' attitudes toward obese intensive care patients. Issue 6 (10th October 2018) - Robstad, Nastasja; Siebler, Frank; Söderhamn, Ulrika; Westergren, Thomas; Fegran, Liv
ABSTRACT: The purpose of this pilot study was to design and test research instruments to measure qualified intensive care nurses' implicit and explicit attitudes and behavioral intentions toward obese intensive care patients. In previous studies researchers have demonstrated that some health professionals hold negative attitudes toward obese patients; however, little is known about qualified intensive care nurses' attitudes toward these patients. Our cross‐sectional pilot study involved Implicit Association Tests, the Anti‐fat Attitude questionnaire, an explicit bias scale comprising ratings of explicit beliefs and feelings, assessment of behavioral intentions based on vignettes, and demographic questions. Thirty qualified intensive care nurses from a general intensive care unit in Norway (80% female; age range 31–62 years) completed the study. Nurses reported implicit and explicit preferences for thin over thick patients and found obese patients lazier than normal‐weight patients. Measures of behavioral intentions and anti‐fat attitudes were reliable. Generally, the nurses intended to help obese patients immediately. Nevertheless, explicit anti‐fat attitudes ( rho = −0.49) as well as implicit anti‐obese stereotypes ( rho = −0.40) were negatively correlated with such intentions. Data supported satisfactory face validity, and convergent and discriminant validity within and between implicit and explicit attitudes and stereotypes. The set of research instruments were reliable, valid, and suitable tools to measure qualified intensive care nurses' implicit and explicit attitudes; however, the present findings need to be replicated in a larger‐scale study.